Phase coherence and phase jumps in the Schwabe cycle. Issue 6 (31st August 2020) - Stefani, Frank; Beer, Jürg; Giesecke, André; Gloaguen, Timo; Seilmayer, Martin; Stepanov, Rodion; Weier, Tom
Abstract: Guided by the working hypothesis that the Schwabe cycle of solar activity is synchronized by the 11.07‐year alignment cycle of the tidally dominant planets Venus, Earth, and Jupiter, we reconsider the phase diagrams of sediment accumulation rates in Lake Holzmaar and of methanesulfonate data in the Greenland ice core Greenland Ice Sheet Project 2 (GISP2), which are available for the period 10000–9000 cal. BP. As some half‐cycle phase jumps appearing in the output signals are, very likely, artifacts of applying a biologically substantiated transfer function, the underlying solar input signal with a dominant 11.04‐year periodicity can be considered to be mainly phase‐coherent over the 1, 000‐year period in the early Holocene. For more recent times, we show that the reintroduction of a hypothesized "lost cycle" at the beginning of the Dalton minimum would lead to a real phase jump. Similarly, by analyzing various series of 14 C and 10 Be data and comparing them with Schove's historical cycle maxima, we support the existence of another "lost cycle" around 1565, also connected with a real phase jump. Viewed synoptically, our results lend greater plausibility to the starting hypothesis of a tidally synchronized solar cycle, which at times can undergo phase jumps, although the competing explanation in terms of a nonlinear solar dynamo with increased coherence cannot be completely ruled out.